"Maybe it's an Indo thing": Transnational health experiences of Indonesian women living in Australia. (May 2023) - Gray, Corie; Crawford, Gemma; Maycock, Bruce; Lobo, Roanna
Abstract: Migrant health-seeking behaviour is understood to be influenced by transnationalism. This paper explores how transnationalism influences health seeking behaviour among Indonesian women living in Perth, Western Australia. Using a participatory action research approach, we conducted five focus groups with 21 women from Indonesia living in Perth. Transnational practices were common amongst Indonesian women. Transnational health-seeking (seeking Indonesian resources in Australia); transnational social support (between countries); and transnational healthcare (return to Indonesia) were common practices amongst Indonesian women. Transnational social networks were a critical source of health information and support. Findings suggest public health interventions may be improved through utilization of transnational social networks. Highlights: Transnational practices appear common among Indonesian migrant women. Health-seeking practices are influenced by transnationalism. Women sought transnational health information; accessed transnational social support; and sometimes returned to Indonesia for healthcare.